PENINGKATAN PENGETAHUAN DAN PEREKONOMIAN IBU-IBU PKK DI DESA BULANGKULON DALAM PENGOLAHAN SAMPAH SEBAGAI BANK SAMPAH - Yudhistira, Nelta Waita; Wulanagustin, Nuri; Prafitri, Apri; Ulun, Ubbayi Khulalul (Jurnal Penamas Adi Buana, 2017)
Garbage problem is often founded in an urban zone as a consequense of urbanization and people activities such happened in Gresik. One of the place in Gresik that always facing rubbish problem is Prambon, Benjeng, Gresik. Garbage bank is an environmental management program and community empowerment. Especially for management of Garbage bank program as a community empowerment because indirectly many people only focus on the enviroronmental management programs. The research problems in this research are : 1) How management of Garbagebnak program as a community empowermwnt is garbage bank Bulangkulon,Prambon, Benjeng,Gresik). 2)What are supporting problems and obstacle factors Gerbage bank program in Bank Sampah Bulangkulon, Prambon. Benjeng Gresik. The objectives in this research are to get description about; 1)The managementof Gerbage abnk program as ab empowering program. 2) Supporing and obstacle factors for gerbage bank program. Gerbage bank program as effort or community become a useful community and impact in family income. But there are still a supporting and interference factor in Gerbage Bank Program. Supporting factors for example : good organization, collaboration with stacholder that good,facility really is equal to, the client is active role. Keywords: Management Gerbage bank program, Community Empowerment.